A Reflection of “Indonesian Maritime Fulcrum” Initiative: Maritime History and Geopolitical Changes - Ismail Ali; Singgih Tri Sulistiyono (Diponegoro University, 2020)
The announcement of a maritime economic initiative known as the 21st Century Maritime Silk Route (MSR) by Chinese President Xi Jinping in 2013 created a new paradigm shift in the geo-economy and geo-politics of countries in the Pacific Ocean and Indian Ocean. With this initiative, China aims to rebuild maritime lines in the seas and oceans where China once was regarded as one of the world's leading powers. In contrast to countries in Southeast Asia, which still hold divergent views on the Chinese initiative, Indonesia sees it as an opportunity to develop regions that have long been marginalized from development. It is in line with the shift in Indonesia’s global economic-political agenda in the 21st century through a doctrine known as